2021
DOI: 10.1007/s10570-021-03937-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical enhancement of cellulose nanofibril (CNF) films through the addition of water-soluble polymers

Abstract: In this work, water-soluble polymers were screened through solution casting and polyvinyl alcohol (PVA) and poly(2-ethyl-2-oxazoline) (PEOX) were found as reinforcement agents for cellulose nano brils (CNFs) lms. Mechanical property increases of 99% in elastic modulus, 93% in the ultimate tensile strength (UTS) and 134% in the work of failure (WOF) were reported for TEMPO-oxidized cellulose nano brils (TOCNF) with 0.44 mmol/g carboxylate groups and 15 wt.% PVA. PEOX had a higher elastic modulus increase of 113… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…Strong interactions may reduce water uptake, limiting or even precluding swelling. Analogous hydrogen bond formation was also observed by Forti et al, who studied the reinforcement of hydrophilic polymers, PVA among them, by using fibril cellulose [28]. It was found that strong hydrogen bond formation between hydroxyl groups of PVA and CNF led to products with increased mechanical properties, an observation in accordance with the conclusion of this study.…”
Section: In Vitro Releasesupporting
confidence: 92%
See 1 more Smart Citation
“…Strong interactions may reduce water uptake, limiting or even precluding swelling. Analogous hydrogen bond formation was also observed by Forti et al, who studied the reinforcement of hydrophilic polymers, PVA among them, by using fibril cellulose [28]. It was found that strong hydrogen bond formation between hydroxyl groups of PVA and CNF led to products with increased mechanical properties, an observation in accordance with the conclusion of this study.…”
Section: In Vitro Releasesupporting
confidence: 92%
“…Novel studies using only a physical crosslinking of PVA with different types of cellulose take advantage of the numerous hydroxyl groups present in PVA chemical structure. Forti et al used PVA of different molecular weights and degrees of hydrolysis and found that a higher hydrolysis level of PVA resulted in CNF/PVA films exhibiting increased mechanical properties [28]. Finally, Song et al also reported physically crosslinked PVA and bacterial cellulose hydrogels, where the incorporation of silver nanoparticles imparted antibacterial properties [29].…”
Section: Introductionmentioning
confidence: 99%